2016
DOI: 10.14238/pi56.3.2016.171-5
|View full text |Cite
|
Sign up to set email alerts
|

Low serum zinc and short stature in children

Abstract: Background Short stature/stunting is common in developing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…The effect of maternal attitude on stunting in children aged 2-3 years The results showed that there was a significant effect between maternal attitudes toward the incidence of stunting through complementary feeding and exclusive breastfeeding. According to Mardewi et al (2016), a positive attitude is one of the determinants of factors that influence exclusive breastfeeding.…”
Section: The Effect Of Maternal Age Onmentioning
confidence: 99%
“…The effect of maternal attitude on stunting in children aged 2-3 years The results showed that there was a significant effect between maternal attitudes toward the incidence of stunting through complementary feeding and exclusive breastfeeding. According to Mardewi et al (2016), a positive attitude is one of the determinants of factors that influence exclusive breastfeeding.…”
Section: The Effect Of Maternal Age Onmentioning
confidence: 99%
“…Beberapa penelitian yang telah dilakukan sebelumnya menjelaskan defisiensi zinc dapat menganggu pertumbuhan bayi dan juga balita, nafsu makan pada bayi dan balita juga dapat menurun sehingga perkembangan motorik juga dapat terhambat 47 .…”
Section: Hasil Dan Pembahasanunclassified
“…Kegagalan untuk mencapai pertumbuhan yang maksimal karena kadar IGF-1 yang berada dalam plasma menurun menyebabkan kadar growth hormone juga mengalami penurunan dah hal ini akan menjadi normal kembali setelah zinc diberikan, selain itu juga menyebabkan anoreksia yang dapat mengakibatkan kurangnya asupan energi dan protein yang diperlukan balita untuk proses pertumbuhan 11,47 .…”
Section: Hasil Dan Pembahasanunclassified
“…16 Deficiency in one of the micronutrients, such as zinc or phosphorus, has been associated with growth retardation. 16,17 Considering the harms of stunted growth in the first two years of life and the importance of diverse and adequate nutritional intake in supporting proper growth of children during the complementary feeding period, we aimed to study these issues. To the best of our knowledge, no such study has been done in Southwest Sumba as one of the highly prevalent areas of stunting in Indonesia.…”
mentioning
confidence: 99%